AGrADC: uma arquitetura para implantação e configuração autônomas de aplicações em grades computacionais - Franco, Sidnei Roberto Selzler (Universidade do Vale do Rio do Sinos, 2007)
Deployment and configuration of grid computing applications are eshaustive and error-prone tasks, representing a weak link of the lifecycle of grid applications. To adress the problem, this work proposes AGrADC, an arquitecture to instantiate grid applications on demand, which incorporates features from the Autonomic Computing paradigm. This architecture improves the grid applications development process, providing tools to define (a) a deployment flow, respecting dependencies among components that comprise the application, (b) configuration paramenters and (c) actions to be executed when adverse situations like faults arise. The result of this process, materialized in the form of a set of descriptions, is delivered to an istantiation engine, which starts to autonomously conduct and manage the deployment and configuration process.
AGrADC: an arquitecture for development and autonomic configuration of the aplications in grid computing
Keywords: autogerenciamento; computação autônoma; grades computacionais; autonomic computing; self-management; grid computing; Ciências Exatas e da Terra